The Relationship Between Abnormal Sleeping Patterns and ADHD - Davis Julia; Lampard James; Dsouza Allen (Journal of ADHD And Care, 2025)
The objective of this focused literature review includes establishing and explaining the high correlation between sleep issues and ADHD. Through a systematic review of sources, a high correlation between sleep issues in those with ADHD was established with multiple theories lending explanation to this comorbidity. Neurological pathways in the brain already afflicted by the disorder of ADHD may cause direct effect on sleep pathways in their dysfunction. Other comorbid sleep conditions were found to occur in high frequency with ADHD however, a common etiology of these issues is yet to be established. The major conclusion of this study includes that there are multiple mechanisms through which sleep disturbances may be caused in ADHD patients, all of which must be considered in future research.
Keywords: ADHD